2019
DOI: 10.1101/841114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seed mass and plant origin interact to determine species germination patterns

Abstract: 1Ongoing changes in temperature and precipitation regime may have strong impact on 2 vulnerable life-history stages such as germination. Differences in germination patterns among 3 species and populations may reflect their adaptation to conditions of their origin or may be 4 determined by the phylogenetic constrains. These two effects are, however, rarely separated. 5 All the germination patterns may also be modified by seed mass. 6 We studied 40 populations of 14 species of Impatiens coming from Himalay… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Finally, the absence of phylogenetic signal in our study may also be because the traits we studied are easier to modify than traits showing high phylogenetic conservatism in previous studies. For example, many previous studies showed strong phylogenetic conservatism in seed size (e.g., Zhang et al, 2004;Moles et al, 2005;Barak et al, 2018) and seed size was in fact shown to be highly phylogenetically conserved in another study in the same system of the genus Impatiens (Veselá et al, 2019). Further studies on phylogenetic patterns of eco-physiological traits within a single genus are thus needed to assess the generality of our findings.…”
Section: Effects Of Phylogenymentioning
confidence: 58%
See 3 more Smart Citations
“…Finally, the absence of phylogenetic signal in our study may also be because the traits we studied are easier to modify than traits showing high phylogenetic conservatism in previous studies. For example, many previous studies showed strong phylogenetic conservatism in seed size (e.g., Zhang et al, 2004;Moles et al, 2005;Barak et al, 2018) and seed size was in fact shown to be highly phylogenetically conserved in another study in the same system of the genus Impatiens (Veselá et al, 2019). Further studies on phylogenetic patterns of eco-physiological traits within a single genus are thus needed to assess the generality of our findings.…”
Section: Effects Of Phylogenymentioning
confidence: 58%
“…As indicated in the methods, our initial sampling has been much more extensive and majority of our material did not germinate and/or survive the initial stages of plant life. The drivers of germination of this seed material have been explored in our previous study (Veselá et al, 2019). Among others, Veselá et al (2019) demonstrated that seeds experiencing warmer temperature, especially leading to shortening of the stratification period, exhibit lower seed germination.…”
Section: Limitations Of the Studymentioning
confidence: 95%
See 2 more Smart Citations
“…This result could indicate that carbohydrates are 509 more effectively used in warm target conditions. In our previous study, we showed, that seed 510 mass interacted with original conditions with higher and faster germination in seed coming 511 from warm and dry localities (Veselá et al 2019). In the current study, we observed a similar 512 trend but only for the interaction of seed mass with original temperature and not moisture.…”
mentioning
confidence: 97%